A regression analysis : Factors that contribute to White-Skin preference among Thai college women - Nualporn Smerasuta (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study aims to examine the relations between white skin preference and the influence of media and advertisement, the influence of significant people, prejudice against dark skin, skin tone esteem, and skin dissatisfaction. In this study, convenience sampling is adopted to recruit one hundred and twelve Thai female college students. A set of questionnaires that assessed five variables were completed by the mentioned target group. A standard multiple regression analysis was conducted on these variables. As predicted, all of our predictors, together, predict white skin preference as high as 74% variance accounted for, (F(5, 106) = 59.10, p < .001). It is found that, out of the five predictors, four of them significantly contribute to white skin preference among Thai college women. These predictors are media and advertisement, significant people, prejudice against dark skin, and skin tone esteem. Even though skin tone dissatisfaction does not significantly contribute to white skin preference, it is important to note that its small contribution as one of the predictors can still be valued. Implications of the findings for future intervention of white skin tone obsession are discussed along with possibilities for future research in this area.